Postnatal Development of Centrifugal Inputs to the Olfactory Bulb - Kostka, Johanna K.; Bitzenhofer, Sebastian H. (Frontiers in Neuroscience, 2022)
Processing in primary sensory areas is influenced by centrifugal inputs from higher brain areas, providing information about behavioral state, attention, or context. Activity in the olfactory bulb, the first central processing stage of olfactory information, is dynamically modulated by direct projections from a variety of areas in adult mice. Despite the early onset of olfactory sensation compared to other senses, the development of centrifugal inputs to the olfactory bulb remains largely unknown. Using retrograde tracing across development, we show that centrifugal projections to the olfactory bulb are established during the postnatal period in an area-specific manner. While feedback projections from the piriform cortex are already present shortly after birth, they strongly increase in number during postnatal development with an anterior-posterior gradient. Contralateral projections from the anterior olfactory nucleus are present at birth but only appeared postnatally for the nucleus of the lateral olfactory tract. Numbers of olfactory bulb projecting neurons from the lateral entorhinal cortex, ventral hippocampus, and cortical amygdala show a sudden increase at the beginning of the second postnatal week and a delayed development compared to more anterior areas. These anatomical data suggest that limited top-down influence on odor processing in the olfactory bulb may be present at birth, but strongly increases during postnatal development and is only fully established later in life.